Державно-приватне партнерство в контексті сталого розвитку: управлінські рішення та екологічні виклики - Berezovskii, P. P. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
This study examines the integration of sustainable development goals within PPPs and the impact of regional environmental challenges on management decision-making. It discusses strategies such as embedding sustainability criteria in contracts, utilizing innovative technologies, and fostering stakeholder engagement to align long-term objectives with immediate actions. The role of regional variations, such as resource availability, socio-economic factors, and regulatory environments, is emphasized as critical to shaping tailored approaches. PPPs are presented as flexible tools that balance economic, social, and environmental priorities through risk-sharing, adaptive decision-making, and sustainable financing methods like green bonds. Additionally, the text explores how integrating ESG criteria and leveraging advanced infrastructure technologies can address regional disparities while enhancing sustainability performance. By focusing on local needs and global directives, the study underscores the importance of PPPs in achieving resilience, fostering innovation, and promoting sustainable development at all levels.